Exploring Islamic Business Materials for English Language Learning among Sharia Economics Students - Tira Nur Fitria; Dewi Muliasari (Jurnal Ilmiah Ekonomi Islam, 2026)
This study explores authentic Islamic Business materials for English language learning among Sharia Economics students, focusing on their types, content, and relevance to students’ academic and professional English needs. This study employs a qualitative descriptive research design. The findings show that authentic Islamic Business materials can provide a relevant and comprehensive foundation for English language learning among Sharia Economics students. The study identifies 40 types of materials covering Islamic banking and finance, halal industries, entrepreneurship, digital finance, social finance, and workplace communication. These include company profiles, banking websites, financial reports, business news, advertisements, social media content, videos, podcasts, interviews, business documents, case studies, business plans, e-commerce content, Islamic fintech materials, halal certification documents, sharia compliance reports, job vacancies, interview materials, customer-service scripts, and Islamic Business regulations. These materials expose students to authentic English used in real Islamic Business contexts and support the development of specialized vocabulary, reading, listening, speaking, writing, and professional communication skills. They also connect English learning directly with students’ academic discipline and potential future careers in Islamic banks, halal businesses, fintech companies, takaful institutions, zakat and waqf organizations, and other Islamic Business sectors. Overall, the findings indicate that integrating authentic, field-related materials can make ESP learning more contextualized, meaningful, practical, and closely connected to students’ real-world academic and professional needs. Future studies are encouraged to develop and validate teaching materials based on the 40 authentic Islamic Business resources identified in this study. Further research could also examine their effectiveness in improving students’ English proficiency, professional communication skills, and readiness for careers in Islamic Business. In addition, lecturers and institutions are encouraged to continuously update authentic materials to reflect developments in Islamic finance, halal industries, fintech, and other emerging sectors.